Implementation of Research Statistics Booklets Assisted Zoom Applications on Student Learning Outcomes - Depi Pramika; Chandra Kurniawan; Zahruddin Hodsay (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: The purpose of this research is to find out the implementation of the zoom application assisted by research statistics booklets on student learning outcomes Design/methodology/approach: The research method used in this study is an experimental method with a quantitative approach. Data collection techniques are done through observation and tests. Data analysis was performed with the Paired Samples Test using the IBM SPSS Statistics 24 tool. Findings: It can be seen from the study results that there is an increase in the value of the average score, i.e., 20.8, from the pretest results of 58.0 (enough criteria) to 78.75 (excellent standards) on the post-test results. The hypothesis test results indicate a significant effect of the zoom application assisted by the research statistics booklet in improving student learning outcomes in the research statistics course. Practical implications: The learning process, especially e-learning, is in dire need of suitable media/tools to support learning, especially practical or computational subjects that require face-to-face explanations even through cyberspace so that learning objectives are achieved, and these media/devices must be supported by internet connectivity with sufficient access. Originality/value: This research results from researcher analysis based on research results to determine the implementation of the zoom application assisted by research statistics booklets on student learning outcomes in semester 5 of the accounting education study program at the University of PGRI Palembang. Paper type: is categorized as a research paper.